KURUMLAR VERGİSİ BAKIMINDAN YABANCI ULAŞTIRMA KURUMLARINDA VERGİLENDİRME SORUNLARI - (:unkn) unknown (My University, 2015)
Yabancı ulaştırma kurumlarının kurumlar vergisine tabi kazancı, KVK m.23'e göre hasılata ortalama emsal oranlarının uygulanması suretiyle hesaplanır. Ortalama emsal oranları, kara taşımacılığında % 12, deniz taşımacılığında % 15, hava taşımacılığında % 5 olarak uygulanır. Yabancı ulaştırma kurumları VUK m.207'ye göre hasılat defteri tutmak zorundadırlar. KVK m.23'e göre hasılat, kara ulaştırmalarında Türkiye sınırları dahilinde gerçekleştirilen faaliyetlerden sağlanan kazançlardan, deniz ve hava ulaştırmalarında ise kalkış noktası olarak Türkiye'deki liman ve havalimanlarının kullanıldığı ulaştırma işlerinden sağlanan kazançlardan oluşur. Ayrıca Türkiye dışındaki taşıma faaliyetleri için diğer kurumlar adına Türkiye'de satılan yolcu ve bagaj biletleri ile yapılan navlun sözleşmelerinden sağlanan komisyon ve ücretlerin hasılata dahil edilmesi gerekir. Türkiye'de işyeri veya daimi temsilci bulundurmak suretiyle ulaştırma faaliyeti yürüten yabancı ulaştırma kurumları bu kazançlarını yıllık beyanname ile beyan etmek zorundadırlar

The taxable income of foreign transportation corporations is calculated by the application of the average equal rates to the revenue in accordance with the article 23 of the Corporate Tax Code. The average equal rates to be applied are 12% for land transportation, 15% for marine transportation and 5% for air transportation. Foreign transportation corporations are to keep the revenue ledger as per the article 207 of the Tax Procedure Code. According to the article 23 of the Corporate Tax Code, the revenue of foreign transportation corporations consists of the income derived from land transportations within Turkey and in marine and air transportations when the departure port is located within Turkey. Furthermore, the commissions and fees that are earned through the sale of passenger tickets and freight contracts on account of the other corporations for their transportation activities outside Turkey should also be added to the revenue. Active foreign transportation corporations that have business premises or agents in Turkey are obliged to complete a tax return for their income
ISSUES ON THE TAXATION OF FOREIGN TRANSPORTATION CORPORATIONS WITHIN THE FRAMEWORK OF CORPORATE TAX
Keywords: Mühendislik, Deniz; Denizcilik